2017
DOI: 10.1177/2394964317721811
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing Relative Customer Value

Abstract: The construct of "value" has been central to explaining economic exchange since the time of Adam Smith. Despite its central importance, debate still exists as to what value entails. Absent a comprehensive understanding of value, researchers and managers have grappled with how to measure and manage value. Not surprisingly, absent a definition, no comprehensive, robust approach has emerged. We argue that value first must be viewed as a dual construct, i.e. value to the customer and value to the firm, that must b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…A good valuation could be a 9 for one customer, while another customer translates it to a 7, so the same qualitative valuation is translated to a different number. The result has been weak relationships between satisfaction and SOP in the literature and challenges by managers as to whether satisfaction and other absolute indicators are useful predictors of customer behavior and business growth (Keiningham et al , 2017; Otto et al , 2020; Reichheld, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A good valuation could be a 9 for one customer, while another customer translates it to a 7, so the same qualitative valuation is translated to a different number. The result has been weak relationships between satisfaction and SOP in the literature and challenges by managers as to whether satisfaction and other absolute indicators are useful predictors of customer behavior and business growth (Keiningham et al , 2017; Otto et al , 2020; Reichheld, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is particularly important because the way customers divide their purchases among competing firms provides the most tangible signal of their perceptions of the relative value these firms provide (Keiningham et al , 2017). The competition serves as a benchmark to evaluate satisfaction with the focal firm, impacting satisfaction scores and indicating the need to know the level of this reference point.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, and although we are aware that, ideally, in an analysis of perceptions and SOW, perceptions should be treated as relative in terms of accounting for the fulfilment that customers perceive from various suppliers (Keiningham et al , 2015b, 2017), data limitations have prevented us from empirically accounting for such relative constructs as the Wallet Allocation Rule (Aksoy, 2014; Keiningham et al , 2015c; Buoye, 2016; Aksoy et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging healthcare practices emphasize a value-driven approach in healthcare management by pressing the need to highlight more at what matters to the patient against what is generally offered in the service provision (Agarwal et al, 2020;Lynn et al, 2015;Keiningham et al, 2017). Agarwal et al (2020) observed that the healthcare landscape is shifting towards emphasizing value over volume (service provisions) as consumer preferences and experiences play a central role in determining healthcare experience.…”
Section: Introductionmentioning
confidence: 99%